2016
DOI: 10.1371/journal.pone.0167104
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure in the Northern Range Margins of Common Ash, Fraxinus excelsior L.

Abstract: During post glacial colonization, loss of genetic diversity due to leading edge effects may be attenuated in forest trees because of their prolonged juvenile phase, allowing many migrants to reach the colonizing front before populations become reproductive. The northern range margins of temperate tree taxa in Europe are particularly suitable to study the genetic processes that follow colonization because they have been little affected by northern refugia. Here we examined how post glacial range dynamics have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 97 publications
2
14
0
1
Order By: Relevance
“…The mean heterozygosity level obtained for 287 Polish ash trees for the nuclear markers (H E = 0.857) was similar to 0.871 reported by Tollefsrud et al (2016) for the same set of markers used to assess 1099 ashes sampled across Europe. Further, Ruņģis et al (2016) reported similar genetic variation for Lithuanian ash trees examined with five Femsatl4, Femsatl10, Femsatl16, Femsatl19 and M2-30 loci.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The mean heterozygosity level obtained for 287 Polish ash trees for the nuclear markers (H E = 0.857) was similar to 0.871 reported by Tollefsrud et al (2016) for the same set of markers used to assess 1099 ashes sampled across Europe. Further, Ruņģis et al (2016) reported similar genetic variation for Lithuanian ash trees examined with five Femsatl4, Femsatl10, Femsatl16, Femsatl19 and M2-30 loci.…”
Section: Resultssupporting
confidence: 73%
“…Those samples were preselected based on mechanoscopy hint (very likely match). The molecular marker set applied to this case study has previously been proven to be highly polymorphic in population-level study of F. excelsior in Europe (Sutherland et al 2010;Tollefsrud et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…; Tollefsrud et al. ). Second, the demographic data reported here suggest persistent expansion and contraction of snook in Texas, and these pulses of abundance at the edge of the species’ range can be expected to be coupled with complementary pulses of gene flow.…”
Section: Discussionmentioning
confidence: 98%
“…The patchiness pattern observed in microsatellite data could be further reinforced by multiple factors associated with the distribution of snook species at the edge of their population ranges. First, Texas represents the leading northern edge of the snook species' range in the western Gulf of Mexico, and previous studies on population leading edges have also observed patterns of disorganized but significant genetic divergence over small spatial scales (Eschbach et al 2014;Shirk et al 2014;Hagen et al 2015;Tollefsrud et al 2016). Second, the demographic data reported here suggest persistent expansion and contraction of snook in Texas, and these pulses of abundance at the edge of the species' range can be expected to be coupled with complementary pulses of gene flow.…”
Section: Population Genetics Of Snook In Texasmentioning
confidence: 99%
“…European ash (Fraxinus excelsior L.) is an important tree species in Europe and a great part of Asia (Kerr & Cahalan, 2004;Fraxigen, 2005;Tollefsrud et al, 2016). Fraxinus is a flexible genus which can be found over a wide range of growing conditionsfrom coastal to mountainous regions, especially on steep slopes (Stöhr & Lösch, 2004), from pioneer to mature woodland, from nutrient-rich to poorer soils (Ferrazzini et al, 2007;Dufour & Piégay, 2008).…”
Section: Introductionmentioning
confidence: 99%